Influenza vaccine related periostitis: A case report of a rare complication - Kaitlyn R. Julian, BS; Kevin Sweetwood, MD; Daria Motamedi, MD (Radiology Case Reports, 2024)
As social distancing guidelines continue to diminish across the country, viral pathogens that were once absent during the COVID-19 pandemic, such as influenza and RSV, have once again become prominent. Although serious side effects of vaccinations are rare, local complications of bursitis and skin and soft tissue infections are well-documented in the literature. We present a case of 1 such rare side effect: influenza vaccine related periostitis. A 39-year-old male patient presented with left shoulder pain which developed 2 days after an influenza vaccination administered to the left deltoid. His symptoms were persistent despite rest and 1 week trial of NSAIDs. MRI imaging demonstrated marrow edema and a periosteal reaction of the left shoulder. Overall, vaccine induced periostitis is poorly documented in the literature and the pathophysiology has not been fully characterized. Further research is crucial to identify patient specific risk factors and to raise awareness of this rare complication to promote swift diagnosis and effective treatment.